Water-soluble, neutral 3,5-diformyl-BODIPY with extended fluorescence lifetime in a self-healable chitosan hydrogel - Senge, Mathias; Belali, Simin; Emandi, Ganapathi; Cafolla, Atillio A.; O'Connell, Barry; Haffner, Benjamin; Karimi, Alireza; Möbius, Matthias E. (My University, 2017)
3,5-Diformyl-4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (3,5-diformyl-BODIPY) can be used as an efficient biofunctional cross-linker to generate a new class of chitosan-based hydrogels with fluorescence resonance energy transfer (FRET) dynamics and good solubility in water. The hydrogel was fully characterized by FT-IR, UV-vis, fluorescence, FE-SEM, AFM, rheology and picosecond time-resolved spectroscopic techniques. The self-healing ability was demonstrated by rheological recovery and macroscopic and microscopic observations. The fluorescence lifetime was found to increase in aqueous solution of the BODIPY-chitosan hydrogel compared to the 3,5-diformyl-BODIPY monomer. Calculations based on experimental results such as red-shift and decreased intensity of the emission spectrum of highly dye-concentrated hydrogel in comparison to dilute hydrogels, together with changes in the fluorescence lifetime of the hydrogel at different concentration of dyes, suggest that the BDP-CS hydrogels fluorescence dynamics obey the Förster resonance energy transfer (FRET). Improvements in mechanical and photochemical properties and the acceptable values of BODIPY fluorescence lifetime in the hydrogel matrix indicate the utility of the newly synthesized hydrogels for biomedical applications.
PUBLISHED
Keywords: Hydrogels; Fluorescence resonance energy transfer (FRET); 4,4‐Difluoro‐4‐bora‐3a,4a‐diaza‐s‐indacene (BODIPY)